2013
DOI: 10.1021/am4037614
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Antiwear Additives in Base Oils: Influence of Structure on Miscibility and Antiwear Performance for Steel on Aluminum

Abstract: The use of ionic liquids as additives to base oil for the lubrication of steel on aluminum was investigated. The miscibility and wear performance of various phosphonium, imidazolium, and pyrrolidinium ionic liquids in a range of polar and nonpolar base oils was determined. The structure and ion pairing of the ionic liquids was found to be important in determining their miscibility in the base oils. In wear tests, some of the miscible base oil/IL blends reduced the aluminum wear depth when compared to that foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
205
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(213 citation statements)
references
References 42 publications
7
205
0
1
Order By: Relevance
“…This fact provoked the introduction of new and more stable ILs based on [FAP] and [NTf 2 ] anions [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], which present enhanced tribological properties due to the formation of fluoride tribofilms, especially at high loads [54]. Recently, phosphonium cation-based ILs have been introduced in this field because of their growing commercial availability and good tribological performance [26,[55][56][57][58][59][60][61][62]. Finally, taking into account the importance of thermal stability in the lifetime of lubricants and additives, the determination of thermal models has become an interesting research topic from scientific and technical points of view.…”
Section: Introductionmentioning
confidence: 99%
“…This fact provoked the introduction of new and more stable ILs based on [FAP] and [NTf 2 ] anions [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], which present enhanced tribological properties due to the formation of fluoride tribofilms, especially at high loads [54]. Recently, phosphonium cation-based ILs have been introduced in this field because of their growing commercial availability and good tribological performance [26,[55][56][57][58][59][60][61][62]. Finally, taking into account the importance of thermal stability in the lifetime of lubricants and additives, the determination of thermal models has become an interesting research topic from scientific and technical points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to commercial lubricating oils of similar viscosities, this IL shows significantly improved friction coefficient and thermal stability. Studies from our group and others have shown that [P6, 6,6,14] + cation based ILs are potential additives for hydrocarbon base oils for a variety of surfaces [19][20][21][22][23][24][25][26][27]. As little as 2 mol% IL dissolved in a base oil lubricates as effectively as the pure IL, and low concentration IL-oil mixtures are much more effective lubricants than the pure base oil [20][21][22], or oils with traditional additives [22,28].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies refer the better solubility of ILs in polar base oils such as ester [41][42][43], polyethylene glycol [44][45][46], or glycerol [47][48][49]. But corrosion is also an important issue in industry [50,51], being closely related to lubrication.…”
Section: Introductionmentioning
confidence: 99%